1985
DOI: 10.1159/000206273
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Abnormalities and Reduced Colony-Forming Cells in Chronic Neutrophilic Leukaemia

Abstract: A case of chronic neutrophilic leukaemia with a 4-year survival is reported. The platelet function is abnormal due to a deficiency of storage pool adenine nucleotides. Neutrophils have a paucity of azurophil and specific granules. Circulating and bone marrow colony-forming cells are markedly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…63 A review of the CNL literature suggested that cytogenetic abnormalities occur in approximately a third of cases, with del(20q) being the most frequent finding. 62,64 Other reported abnormalities include trisomy 8, 65 trisomy 21 66 and t(1;20), 67 although none are specific for CNL. A normal karyotype, however, characterizes the majority of cases, a finding that suggests that the initial genetic event is submicroscopic and not visible by conventional cytogenetic analysis.…”
Section: Chronic Neutrophilic Leukaemiamentioning
confidence: 99%
“…63 A review of the CNL literature suggested that cytogenetic abnormalities occur in approximately a third of cases, with del(20q) being the most frequent finding. 62,64 Other reported abnormalities include trisomy 8, 65 trisomy 21 66 and t(1;20), 67 although none are specific for CNL. A normal karyotype, however, characterizes the majority of cases, a finding that suggests that the initial genetic event is submicroscopic and not visible by conventional cytogenetic analysis.…”
Section: Chronic Neutrophilic Leukaemiamentioning
confidence: 99%
“…These findings suggest that at least in some CNL cases oncogenesis occurs at the level of hematopoietic stem cells [4]. On the other hand, it has also been suggested from the results of clonal cell assays that CNL occurs at the level of granulocyte-committed progenitors [5, 6]. We present here a case of CNL that subsequently transformed to acute myeloblastic leukemia (AML) with dysplastic features in the granulocytic lineage and myelofibrosis.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, a series of case reports demonstrated severe bleeding complications in CNL patients (7,8), which suggests that CNL is correlated with increased bleeding; however, the precise pathological mechanism of this relationship remains unclear. Elliott suggested that the bleeding complications observed in patients with CNL are associated with treatment-induced thrombocytopenia (6); however, some case reports have indicated the presence of platelet dysfunction in these patients (7,(9)(10)(11)(12). The majority of CNL patients presenting with platelet dysfunction were reported before the establishment of the WHO 2008 diagnostic criteria for CNL.…”
Section: Discussionmentioning
confidence: 99%